Opening a window into the riddle of misophonia, sensory over-responsiveness, and pain - Efraim Kaufman, Adi; Weissman-Fogel, Irit; Rosenthal, M. Zachary; Kaplan Neeman, Ricky; Bar-Shalita, Tami (Frontiers in Neuroscience, 2022)
Misophonia and sensory over-responsiveness (SOR) share physiological and psychological symptoms. While individuals with SOR demonstrate pain perception alterations, these were not explored in misophonia. Methods: This exploratory study comprised thirty healthy adults with [n =15; based on the Misophonia Questionnaire] and without misophonia. The Sensory Responsiveness Questionnaire (SRQ) was used for evaluating sensory responsiveness. In addition, psychophysical tests were applied for quantification of: (i) stimulus-response function of painful stimuli, (ii) the individual perceived pain intensity (iii) pain modulation efficiency, (iii) auditory intensity discrimination capability, and (iv) painful and unpleasantness responses to six ecological daily sounds using the Battery of Averseness to Sounds (BAS). Results: Individuals with misophonia reported higher scores in the SRQ-Aversive (p = 0.022) and SRQ-Hedonic (p = 0.029) scales as well as in auditory (p = 0.042) and smell (p = 0.006) sub-scales, indicating higher sensory responsiveness. Yet they were not identified with the SOR type of sensory modulation dysfunction. Groups did not differ in the pain psychophysical tests, and in auditory discrimination test scores (p>0.05). However, in the misophonia group the BAS evoked higher pain intensity (p = 0.046) and unpleasantness (p <0.001) ratings in the apple biting sound, and higher unpleasantness rating in the scraping a dish sound (p = 0.007), compared to the comparison group. Conclusions: Findings indicate increased sensory responsiveness in individuals with misophonia, yet not defined as SOR. Thus, this suggests that misophonia and SOR are two distinct conditions, differing in their behavioral responses to painful and non-painful stimuli. .